Relationships between propulsion and anthropometry in Paralympic swimmers - Dingley, A. A.; Pyne, D. B.; Burkett, B. J. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To characterize relationships between propulsion, anthropometry, and performance in Paralympic swimming. Methods: A cross-sectional study of swimmers (13 male, 15 female) age 20.5 ± 4.4 y was conducted. Subject locomotor categorizations were no physical disability (n = 8, classes S13-S14) and low-severity (n = 11, classes S9-S10) or midseverity disability (n = 9, classes S6-S8). Full anthropometric profiles estimated muscle mass and body fat, a bilateral swim-bench ergometer quantified upper-body power production, and 100-m time trials quantified swimming performance. Results: Correlations between ergometer mean power and swimming performance increased with degree of physical disability (low-severity male r = .65, ±0.56, and female r = .68, ±0.64; midseverity, r = .87, ±0.41, and r = .79, ±0.75). The female midseverity group showed near-perfect (positive) relationships for taller swimmers` (with a greater muscle mass and longer arm span) swimming faster, while for female no- and low-severity-disability groups, greater muscle mass was associated with slower velocity (r = .78, ±0.43, and r = .65, ±0.66). This was supported with lighter females (with less frontal surface area) in the low-severity group being faster (r = .94, ±0.24). In a gender contrast, low-severity males with less muscle mass (r = -.64, ±0.56), high skinfolds (r = .78, ±0.43), a longer arm span (r = .58, ±0.60) or smaller frontal surface area (r = -.93, ±0.19) were detrimental to swimming-velocity production. Conclusion: Low-severity male and midseverity female Paralympic swimmers should be encouraged to develop muscle mass and upper-body power to enhance swimming performance. The generalized anthropometric measures appear to be a secondary consideration for coaches.